Stygofaunal community trends along varied rainfall conditions: Deciphering ecological niche dynamics of a shallow calcrete in Western Australia. Issue 1 (10th December 2019) - Saccò, Mattia; Blyth, Alison J.; Humphreys, William F.; Karasiewicz, Stéphane; Meredith, Karina T.; Laini, Alex; Cooper, Steven J.B.; Bateman, Philip W.; Grice, Kliti
Abstract: Groundwaters host highly adapted fauna, known as stygofauna, which play a key role in maintaining the functional integrity of subterranean ecosystems. Stygofaunal niche studies provide insights into the ecological dynamics shaping the delicate balance between the hydrological conditions and community diversity patterns. This work aims to unravel the ecological trends of a calcrete stygofaunal community, with special focus on niche dynamics through the Outlying Mean Index analysis (OMI) and additional calculation of Within Outlying Mean Indexes (WitOMI), under three rainfall regimes. Temperature and pH changed significantly among different rainfall conditions ( P < .001), and together with salinity were the most influential drivers in shaping stygofaunal assemblages. These environmental conditions, linked with nutrient fluctuations in the groundwater, constrained changes in niche occupation for water mites, two species of beetles and juvenile amphipods (OMI analysis, P < .05). The WitOMI analysis revealed differential subniche breadths linked with taxa‐specific adaptations after different rainfall conditions. Our results indicate that stygofaunal niches are closely linked to the hydrodynamic conditions influenced by different rainfall regimes. Further long‐term investigations, incorporating broader ecological perspectives, will help to understand the impacts associated with climate change and anthropogenic pressures on one of the most threatened ecosystems in the world.